The Sacco-Vanzetti Affair : America on trial - Temkin, Moshik, 1971- (Yale University Press, 2009)
What began as the obscure local case of two Italian immigrant anarchists accused of robbery and murder flared into an unprecedented political and legal scandal as the perception grew that their conviction was a judicial travesty and their execution a political murder. This book is the first to reveal the full national and international scope of the Sacco-Vanzetti affair, uncovering how and why the two men became the center of a global cause célèbre that shook public opinion and transformed America's relationship with the world. Drawing on extensive research on two continents, and written with verve, this book connects the Sacco-Vanzetti affair to the most polarizing political and social concerns of its era. Moshik Temkin contends that the worldwide attention to the case was generated not only by the conviction that innocent men had been condemned for their radical politics and ethnic origins but also as part of a reaction to U.S. global supremacy and isolationism after World War I. The author further argues that the international protest, which helped make Sacco and Vanzetti famous men, ultimately provoked their executions. The book concludes by investigating the affair's enduring repercussions and what they reveal about global political action, terrorism, jingoism, xenophobia, and the politics of our own time.